Effect of densification on the ferroelectric response of Ba0.4Sr0.6TiO3. (March 2015) - Jaffari, G. Hassnain; Iqbal, M. Asad; Hasanain, S.K.; Ali, Awais; Bhatti, A.S.; Shah, S. Ismat; Mumtaz, Arif
Abstract: A comprehensive comparative study of the frequency response of the dielectric constant of bulk Barium Strontium Titanate Ba0.40 Sr0.6 TiO3 sintered at 1000 °C and 1400 °C is presented. Crystal structure and electronic structure studies were found to be identical for both samples; however, dielectric properties revealed drastic differences. Dielectric response as a function of temperature and frequency show that sintering at higher temperatures yields samples with an order of magnitude enhancement in the magnitude of the dielectric constant and sharp, non-dispersive ferroelectric transitions. At lower temperature, on the other hand, synthesis results in relaxor like features for the same composition. Hence microstructural analysis was carried out which showed pellets sintered at low temperatures exhibits features such as porosity and were less dense compared to the ones annealed at higher temperatures. This suggests that relaxor-like behavior cannot be related strictly to composition. In general sample porosity, homogeneity, etc., have to be taken into account as well. Highlights: Frequency response of the dielectric constant of Ba0.4 Sr0.6 TiO3 sintered at various temperatures. Crystal and electronic structure is identical for both low and high temperature sintering. This ferroelectric composition is specifically chosen to observe all the structural transitions. Lower temperature sintering led to the observation of single diffused and dispersive FE transition. Pellets sintered at low temperatures exhibited higher porosity. Relaxor-like behavior of composition being FE, is related to porosity, homogeneity etc.